The features and trends of out-of-hospital cardiac arrests in Japanese working generation: long-term aspects of a prospective, nationwide, population-based registry. (25th November 2020) - Yamagishi, Y; Oginosawa, Y; Miyamoto, T; Tukahara, K; Ohe, H; Kohno, R; Otsuji, Y; Abe, H
Abstract: Background: Despite sudden cardiac death (SCD) in working generation is a crucial issue in terms of public health, social and economic significance, the long-term SCD condition in working generation is unclear. Purpose: This study aimed to clarify the features and long-term trends of SCD in working generation from 2005 through 2016 in Japan, using a prospective, nationwide, population based out-of-hospital cardiac arrest (OHCA) registry. Methods: We performed data analysis of the nation-wide registry in Japan who experienced OHCA during the 12 years. Working generation was defined as 20 to 69 years and we analyzed only definitive cardiogenic OHCA as an approximation of SCD. Results: The number of definitive cardiogenic OHCA of working generation during the period was 66, 214 and 31% of the events in whole population was working generation. Definitive cardiogenic OHCA in working generation in terms of both number and percentage of the population had been decreased from 6522 (0.07‰) in 2005 to 4910 (0.06‰) in 2016, bystander cardiopulmonary resuscitation (CPR) and usage of automated external defibrillator (AED) ratio increased from 32.7% in 2005 to 49.6% in 2016, and 0.3% in 2005 to 14.7% in 2016 respectively, and the survival rate after one-month improved year by year, from 12.8% in 2005 to 34.0% in 2016 (picture below). Among non-medical bystanders, CPR was most often performed by colleagues in this generation, while AED use rate by colleague was smaller, and the time from witness to initial defibrillation was significantly longer than by passerby. Good prognosis was observed in terms of one-month survival ratio and neurological outcome for those undergoing CPR by colleague and passerby compared with other bystanders. For 12 years, although the degree varies, all non-medical bystander had same tendency; bystander CPR and usage of AED ratio increased, and the survival rate after one-month and neurological outcome improved year by year. Conclusions: Not only the number but the incidence of cardiogenic OHCA in working generation has been decreased in Japan. The positive prognosis of this generation may be related to CPR by colleagues. Funding Acknowledgement: Type of funding source: None